Anatomic study of the superior glenoid labrum. Issue 3 (21st September 2012) - Bain, Gregory I.; Galley, Ian J.; Singh, Charanjeet; Carter, Chris; Eng, Kevin
Abstract The purpose of the study was to describe the normal anatomy of the glenoid labrum to help identification of pathology and guide surgical repair. Twenty dry bone scapulae and 19 cadaveric shoulders were examined. Light microscopy was performed on 12 radial slices through the glenoid. An external capsular circumferential ridge, 7–8 mm medial to the glenoid rim marks the attachment of the capsule. A separate internal labral circumferential ridge 4 mm central to the glenoid rim marks the interface between the labrum and articular cartilage. A superior–posterior facet was found consistently on the glenoid. Two thirds of the long head of biceps arises from the supraglenoid tubercle, 6.6 mm from the glenoid face, the remainder from the labrum. The superior labrum is concave and is loosely attached to the articular cartilage and glenoid rim. Clefts and foramens are common superiorly. In contrast the anterior–inferior labrum is convex, attaches 4 mm central to the glenoid rim and has a strong attachment to articular cartilage and bone. Sublabral clefts, recesses, and holes are common, but only in the superior–anterior labrum. Lesions in other regions of the labrum are potentially pathological. A complex superior labrum tear that extends to involve the biceps anchor, should have the biceps anchor repaired to the supraglenoid tubercle (mean 6.6 mm off the glenoid face) and the labrum be repaired to the glenoid rim. The anteroinferior labrum should be repaired 4 mm onto the glenoid face. This study will aid in identifying pathological labral lesions and guide anatomic repairs. Clin. Anat., 2013. © 2012 Wiley Periodicals, Inc.